A pílula mágica e o (pré)conceito: a realidade e o impacto da leucemia mielóide crônica na vida do paciente - Lombardo, Mariela Santos [UNESP] (2014)
The advent of specific drug target for the treatment of Chronic Myeloid Leukemia (CML) in 2001, maybe will score a few more glory days in the history of fighting cancer. These drugs are the result of high medical technology and promise a better control of the CML with reduced side effects, by reference to those of conventional chemotherapy. Cancer is a chronic disease feared and stigmatized in our society that generally impacts the physical and mental body of its bearer. However, cancer has been recognized even more as a manageable disease and that it can take a long survival to its carrier, allowing them to maintain their life goals and their routine activities in different dimensions of everyday life. The myths and beliefs around cancer take on a singular character by reference to other chronic diseases, with a perception of unpredictability in the carrier and his family. This study investigated the experience of illness and the impact of CML in daily life as well as the perception of the carrier on the disease process, treatment and the impact of the disease in its life relationship. Seven semi-structured interviews with two women and five men with CML were performed. A thematic content analysis of the data produced was guided by an adaptation of the proposed Bardin. We found that experiences of illness are initially perceived by various physical manifestations and, in general, rather weak, but sufficient for some subjects seek to clarify them. The diagnosis of CML caused an impact on the lives of the subjects, marking a before and an after, caused by different changes in everyday life: the long-term treatment (although lighter than chemotherapy), routine visits to the hospital for appointments and tests, disturbances and changes in work relationships, personal and family. Subjects found different explanations for such misfortune, some of them linked to previously work and products used ...